Cultura visual, cultura digital e a arte/educação - Finn, Renata Santos (My University, 2022)
This course conclusion work aimed to identify students' responses and reflections on the impacts on the use of media and technologies in visual arts classes, as well as trying to understand how visual culture and digital culture manifested in the context of students in a class of High School in a school in Caxias do Sul. The methodological proposal used to account for the objectives emerges from the internship experience of the author of this TCC, carried out in the first semester of 2021. This study aims to understand the importance of teaching visual arts that take into account the contemporaneity and its impacts, making it necessary to address the culture in which students are inserted, a culture that is largely based on digital technologies. For this, it was also necessary to understand how digital technologies are present in schools. The study conceptualizes culture in a broad way, approaching the historicity of the word, based on Antonio Gramsci's thought. The second moment is dedicated to digital culture, characterizing it according to Castells. The third moment is dedicated to organizing curricula focused on the present through visual culture. Fernando Hernandez, with his studies, contributes to the dialogue about "critical visual literacy" and the interests of today's students. In the fourth moment, the focus is on the inseparability between contemporaneity and visual culture, according to ideas by Hernández and contributions by Eloiza Gurgel Pires. The fourth chapter addresses the contemporary teaching of Art/Education, based on the studies of Ana Mae Barbosa. Finally, with theoretical input from Kerry Freedman, Christine Ballenge-Morris, Vesta Daniel and Patricia Stuhr who help to reflect on non-academic knowledge within the school environment, highlighting multiculturalism and intercultural territory, examples are presented of how visual culture and digital culture reverberate in the Visual Arts classes. To this end, materials produced during the pandemic are used by first-year high school students at the Evaristo de Antoni school, in Caxias do Sul, during the classes of Stage III, of the Licentiate Course in Visual Arts at the University of Caxias do Sul. [resumo fornecido pelo autor]
Este trabalho de conclusão de curso objetivou identificar respostas e reflexões dos alunos mediante os impactos no uso das mídias e das tecnologias nas aulas de artes visuais, bem como tentou compreender como a cultura visual e a cultura digital se manifestaram no contexto de estudantes de uma turma de Ensino Médio em uma escola de Caxias do Sul. A proposta metodológica utilizada para dar conta dos objetivos emerge da experiência de estágio da autora deste TCC, realizada no primeiro semestre de 2021. Este estudo tem como propósito, compreender a importância de um ensino de artes visuais que leve em conta a contemporaneidade e seus impactos, sendo necessário abordar a cultura em que os estudantes estão inseridos, cultura essa pautada em boa parte pelas tecnologias digitais. Para isso, também foi preciso entender de que maneira as tecnologias digitais estão presentes nas escolas. O estudo conceitualiza a cultura de forma ampla, abordando a historicidade da palavra, a partir do pensamento de Antonio Gramsci. O segundo momento é dedicado à cultura digital, caracterizando-a segundo Castells. O terceiro momento é dedicado à organização curricular voltada para a atualidade por meio da cultura visual. Fernando Hernandez com seus estudos contribui para o diálogo a respeito do "alfabetismo visual crítico" e os interesses dos estudantes de hoje. No quarto momento o foco está na indissociação entre a contemporaneidade e a cultura visual, conforme ideias de Hernández e contribuições de Eloiza Gurgel Pires. O quarto capítulo aborda o ensino contemporâneo da Arte/Educação, com base nos estudos de Ana Mae Barbosa. Por fim, com aporte teórico de Kerry Freedman, Christine Ballenge-Morris, Vesta Daniel e Patricia Stuhr os quais auxiliam a refletir sobre os conhecimentos não acadêmicos dentro do ambiente escolar evidenciando o multiculturalismo e o território intercultural, são apresentados exemplos de como a cultura visual e a cultura digital repercutem nas aulas de Artes Visuais, para tanto, são utilizados materiais produzidos durante a pandemia pelos estudantes do primeiro ano do Ensino Médio da escola Evaristo de Antoni, de Caxias do Sul durante as aulas do Estágio III, do Curso de Licenciatura em Artes Visuais da Universidade de Caxias do Sul. [resumo fornecido pelo autor]
Keywords: Arte; Educação; Arte e tecnologia; Cultura e tecnologia